2015
DOI: 10.1002/elps.201500186
|View full text |Cite
|
Sign up to set email alerts
|

Development of a capillary zone electrophoresis method for dose determination in a tetravalent dengue vaccine candidate

Abstract: Dengue is known to cause morbidity and mortality worldwide and currently there is neither available specific therapeutics to treat nor a vaccine to prevent this disease. Although efforts are being made, development of a vaccine against this disease remains challenging. Hawaii Biotech Inc developed a recombinant subunit envelope protein-based vaccine against all four serotypes produced in Drosophila S2 cells which were transferred over to Merck in 2010. Each subunit of the four dengue serotypes contains the N-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Interestingly, Hamm et al. observed peak tailing of the tetravalent dengue vaccine using different HPMC batches. A binding of the sample molecules to HPMC was assumed.…”
Section: Capillary Zone Electrophoresismentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Hamm et al. observed peak tailing of the tetravalent dengue vaccine using different HPMC batches. A binding of the sample molecules to HPMC was assumed.…”
Section: Capillary Zone Electrophoresismentioning
confidence: 99%
“…Hamm et al. developed a concentration assay for the tetravalent dengue vaccine. Due to the nonavailability of suitable antibody reagents against each dengue serotype, the use of ELISA was difficult.…”
Section: Capillary Zone Electrophoresismentioning
confidence: 99%
“…As described earlier , CZE has been used for stability indicating methods, e.g. for recombinant human interleukin‐11 and oxytocin , as well as for the dose‐determination of a dengue fewer vaccine candidate .…”
Section: Determination Of (Bio)pharmaceuticalsmentioning
confidence: 99%
“…For this purpose, a CZE–CZE–MS approach was published recently . Due to the individual properties of different biopharmaceuticals, various modifications of the initial method from He and colleagues have been published . Goyon et al.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, a CZE-CZE-MS approach was published recently [10]. Due to the individual properties of different biopharmaceuticals, various modifications of the initial method from He and colleagues [8] have been published [11][12][13]. Goyon et al demonstrated an alternative approach for the analysis of charge variants of mAbs using a BGE containing polyethylene oxide for dynamic coating and Bis-tris as a buffering agent.…”
Section: Introductionmentioning
confidence: 99%